SISTEM PAKAR UNTUK PEMILIHAN GITAR LISTRIK MENGGUNAKAN METODE CERTAINTY FACTOR PADA TOKO ALAT MUSIK SUNYOTOK - Nor Hikmah; Adim Sahrial (Information System Journal, 2022)
Guitar is one of the most popular and easy to find instruments in people's lives, from children to parents who like guitar instruments. But in searching for a guitar or buying a guitar, many are wrong in choosing a guitar because it does not match the genre of music being played.In this research, an analysis of existing problems is carried out, the author tries to create a web-based expert system that can help solve existing problems. This research uses the certainty factor method. The application development stage begins with the stages of problem analysis, system design, designing system process models, interface design, and relations between tables.The application made is a web-based expert system to help in choosing the best guitar according to the criteria entered into the system, and displaying presentations in the guitar choices given as well as a detailed explanation of the guitar. Expert systems are built using the PHP programming language, MySQL database server, and sublime text as a text editor.